Leading with an Inclusion Mindset: Strategic Recommendations for School Leaders and Administrators - Keeley, Randa; Peterson-Ahmad, Maria; Beecher, Schuyler (Social Education Research, 2026)
The successful inclusion of students with disabilities in general education settings is heavily dependent on the strategic leadership and systemic support provided by school administrators. Administrators can support the inclusion of students with disabilities in the general education classroom by promoting differentiated professional development opportunities in an effort to advance in continuous improvement and raise student achievement in their classrooms. Instructional constructs such as Universal Design for Learning (UDL) framework, Evidence-Based Practices (EBPs), and High Leverage Practices (HLPs) can be implemented to support the inclusion of students with disabilities in the general education classroom. This literature review provides evidence-based recommendations for administrators, including the deliberate allocation of resources, protected collaborative planning time, and targeted professional development in UDL, EBPs, and HLPs to ignite school-wide change. By aligning district policy with equitable pedagogical practices and supporting teacher efficacy, administrators can move beyond philosophical endorsement to create sustainable, district-wide inclusion that recognizes and celebrates the unique profiles of all learners.